Fatores associados à qualidade de vida em idosos com osteoartrite de joelho - Alexandre, Tiago Da Silva (2008)
This study inquired whether quality of life (QoL) among elderly patients with knee osteoarthritis (OA) may be influenced by sociodemographic and/or clinic and functional factors. A sample of 40 elderly outpatients from a gerontological rehabilitation service in São Paulo answered the Brazilian version of the 36-Item Short Form Survey (SF-36). Functionality, joint stiffness and pain were assessed by the Womac - Western Ontario and MacMaster Universities Osteoarthritis Index. Further data on sociodemographic and clinical features, including pain-relieving strategies, were obtained by a complementary questionnaire. By means of linear regression analysis, an independent relationship was found between the Womac functionality domain and six SF-36 domains (p<0.05). In the studied sample, poor QoL was found to be correlated to difficulty in functional activities, using a gait assistive device, to present bilateral knee impairment, to resort to several means to relieve pain, as well being illiterate and living with another elderly (r=0.3; p<0.05). The most impaired functional activities were those that involve knee flexion and extension, and weight support on the affected limb. Both sociodemographic and clinical, functional factors generated by OA negatively influenced QoL of elderly patients with knee OA.